(untitled) (Boca Raton, 2004)
Coffee, tea, and chocolate are among the most frequently consumed products in the world. The pleasure that many experience from these edibles is accompanied by a range of favorable and adverse effects on the brain that have been the focus of a wealth of recent research.
Công nghệ chế biến chè, cà phê, ca cao
Keywords: Caffeine,Caffeine,Cà phê,Chất caffein,Caffeine,Caffeine,Brain,Não; Physiological effect.,Pharmacology.,Tác dụng sinh lý,Dược lý,Physiological effect.,Tác dụng sinh lý.,Physiology,Sinh lý học